ELECTROTECHNOLOGICAL PROCESSING OF SUNFLOWER SEEDS WITH ULTRAVIOLET LIGHT - Uktomjonov, Shermurod (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The article presents the results obtained from ultraviolet irradiation of sunflower seeds in order to obtain higher yields from sunflower, among other agrotechnical measures, to improve the quality indicators of seeds prepared for planting, to obtain better seeds with high germination and potential yield in laboratory and field conditions. Determination of optimal values of parameters and modes of operation of these sunflower seeds with ultraviolet light was studied, including the results of the study of the duration of irradiation of seeds and the distance from the irradiator to the seed.